The Reds The Communist Party of Australia from origins to illegality - Macintyre, Stuart 1947- (Allen & Unwin, 2022)
In 1920, 26 men and women met in a dingy hall in Sydney to create a new political party. They expected the overthrow of capitalism and the emancipation of humanity - here, and all around the world. Two decades later, when Australia joined the Second World War, the Commonwealth government suppressed the Communist Party of Australia. The handful of idealists and dissidents had become a political force powerful enough, in the view of the authorities, to pose a threat to national security. The Communist Party was a major part of Australia's political landscape for more than half a century. It played a vital role in the country's largest trade unions. It blazed a trail for a range of social movements and attracted writers and artsists who influenced much of Australia's cultural life. It also became the target of sustained surveillance and penetration by state police and federal security agencies. Stuart Macintyre's account is the first comprehensive study of Australian communism in its formative years
Keywords: Communist Party of Australia; Geschichte 1920-; Political history; Political parties & ideologies inc individual politicians; Communist Party of Australia / History; Communism / Australia; Communism / Australia / History; Political parties / Australia; Australia / Politics and goverment / 1901-1945; Communism; Political parties; Australia; 1901-1945; History